Afro-Asian Film Festival III: Women’s Knowledge and Imagination in Film Sovereignity - Siagian, Bunga Pratiwi; Kurnia, Lilawati (Capture : Jurnal Seni Media Rekam, 2023)
This article examines the third edition of the Afro-Asian Film Festival (AAF), held in Jakarta in 1964. A series of film festivals that serve as a container of meetings between newly independent and still colonized nations to articulate the political expressions of the third world. The festival was studied with a qualitative-descriptive approach. Analysis of his research data through textual and contextual reading of available archival material, such as film plays, delegation speeches, communiques, and newspaper coverage, involving theoretical ideas of Peripheral Marxism. There are two findings, firstly, showing the ideological contribution of the left that makes FFAA III more radical than the previous two editions of the FFAA. Secondly, a textual analysis of the two winning films shows the role of FFAA III in giving space to issues and knowledge generated by women. FFAA III articulates anti-colonial third-world political expressions as well as anti-imperialist leftist thinking based on the objective everyday realities of third-world people, which in this paper appear in the percolation of women living in feudal cultures. The findings of this research are useful in enriching knowledge of the history of film in the era of independence and adding to the spirit of nationalism. Keywords: Afro-Asia Film Festival; Indonesian; women studies; leftist ideology